2019
DOI: 10.1002/ece3.4943
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic diversity in aposematic Malagasy poison frogs (genus Mantella)

Abstract: Intraspecific color variation has long fascinated evolutionary biologists. In species with bright warning coloration, phenotypic diversity is particularly compelling because many factors, including natural and sexual selection, contribute to intraspecific variation. To better understand the causes of dramatic phenotypic variation in Malagasy poison frogs, we quantified genetic structure and color and pattern variation across three closely related species, Mantella aurantiaca , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 110 publications
(193 reference statements)
0
7
1
Order By: Relevance
“…Similar to our results, their study found clear genetic clusters that did not align with current species designations, and supported a substantial genetic differentiation between yellow- and green-colored populations of M. crocea . However, the RADseq data [82]—obtained from different individuals and partly different populations than our microsatellite data—found strong indication of admixture at several sites, and an intriguing pattern of genetic clustering of yellow-colored M. crocea specimens with M. aurantiaca , not recovered by our study. These results reinforce our conclusion that the taxonomy of this complex of frogs is convoluted but without an obvious and simple resolution in sight, despite an increasing body of detailed population genetic and population genomic data.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Similar to our results, their study found clear genetic clusters that did not align with current species designations, and supported a substantial genetic differentiation between yellow- and green-colored populations of M. crocea . However, the RADseq data [82]—obtained from different individuals and partly different populations than our microsatellite data—found strong indication of admixture at several sites, and an intriguing pattern of genetic clustering of yellow-colored M. crocea specimens with M. aurantiaca , not recovered by our study. These results reinforce our conclusion that the taxonomy of this complex of frogs is convoluted but without an obvious and simple resolution in sight, despite an increasing body of detailed population genetic and population genomic data.…”
Section: Discussioncontrasting
confidence: 69%
“…While the present paper was under final review, Klonoski et al [82] published a population genomic analysis of M. aurantiaca , M. crocea and M. milotympanum using restriction site-associated DNA (RAD) sequencing. Similar to our results, their study found clear genetic clusters that did not align with current species designations, and supported a substantial genetic differentiation between yellow- and green-colored populations of M. crocea .…”
Section: Discussionmentioning
confidence: 99%
“…More consistent IBD patterns were recovered by analyses based on genotype likelihoods than by analyses based on SNP calling, whose significance varied, but not systematically in the same direction, depending on the level of missing data. Our results therefore support the idea that analyses based on genotype likelihoods perform better than analyses based on genotype calls with NGS data characterized by low read depth and high levels of missing data (Korneliussen et al ., 2014; Meisner & Albrechsten, 2018; Klonoski et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Geographic variation in host-defense polypeptides is correlated with color pattern in red-eyed treefrogs, indicating a role for ecological selection (Davis et al 2016, Clark in prep.). Aposematic coloration is common among other brightly colored anurans (e.g., many species within Dendrobatidae, Mantellidae), and has been shown to vary among and within populations (Klonoski et al, 2019; Maan & Cummings, 2008; Rojas et al, 2014; Roland et al, 2017; Summers & Clough, 2001; Tarvin et al, 2017). Variation in the color pattern of aposematic species is often attributed to the interplay between ecological and sexual selection (Maan & Cummings, 2008; Nokelainen et al, 2012; Rojas & Endler, 2013).…”
Section: Resultsmentioning
confidence: 99%